DMC Based on Weighting Correction of Predictive Model Errors - Liu Yumin; Sun Yonghe; XU Fengming; Wang Tao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Ordinary dynamic matrix predictive control (DMC) correct predictive value only using current error, so the correction is not enough. This paper proposes an algorithm. In error correction, it introduces predictive model error and predictive value are weighting corrected to improve the capability of resisting disturbance and regulating speed of the control system. By theoretical analysis and simulation, it has been proven that the algorithm is effective. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2428